ผลการใช้รูปแบบการเรียนการสอนด้วยยุทธศาสตร์สะท้อนอภิปัญญาร่วมกับการเรียนรู้ โดยใช้การวิจัยเป็นฐาน: กรณีศึกษารายวิชาภาษาไทย สังคมศึกษา และวิทยาศาสตร์ - วังแก้วหิรัญ, ทิพย์วิมล (Journal of Applied Economics and Management Strategy, 2018)
The objectives of this research were to study the results of using an instructional model based on reflective metacognition strategies together with research-based learning (KWPML plus RBL) in terms of the evaluation of learning achievement in Thai, social study, and science subjects. The samples were grade VI students from 3 classrooms at Tessaban 2 Phayasrisoontornvoharn (Noi Ajarayangkul) School in Thailand, and simple random sampling was used to select the samples. The data analysis was conducted using average and standard deviation. The hypothesis was tested using dependent t-test. The findings revealed the following. The students’ learning achievement posttest for the Thai subject unit topic “Why proverbs are important!” was higher than for the pretest at the significance level of .01. In the same way the students’ learning achievement the posttest for the social study subject unit topic “Physical characteristics and natural phenomena” was higher than for the pretest at the significance level of 0.01. The students’ learning achievement posttest for the science subject unit topic “Everyday substance” was higher than for the pretest at the significance level of 0.01. Most of the research process skills of students in the Thai, social study, and science subjects were at a very good level in terms of problem identification, hypothesis setting, hypothesis testing, data collection, data analysis and summarizing, and presentation and evaluation. The data analysis and summarizing skill was the skill that all students were seen to have at a very good level. In addition, the students’ satisfaction with the instructional model was at the highest level. Keywords: Instructional Model, Metacognition, Research-Based Learning